Assessing the utilization of HIV genotype resistance testing: Insight from Italian Infectious Diseases Units - Andrea De Vito; Antonia Bezenchek; Rossana Scutari; Luna Colagrossi; Giacomo Valenti; Maria Concetta Bellocchi; Luca Pipitò; Sergio Ferrara; Sergio Malandrin; Monica Tallarita; Alessandro Cozzi-Lepri; Francesca Ceccherini-Silberstein; et al. (Journal of Global Antimicrobial Resistance)
Purpose: We aimed to assess the utilization of genotype resistance testing (GRT) by Infectious Diseases Units across Italy. Methods: A cross-sectional study was conducted involving a questionnaire distributed to the Infectious Diseases Unit in Italy. A web-based survey using Google Forms software was utilized and spread via email or cellphone. Results: Responses were obtained from 101 Infectious Diseases Units. Among these centres, only seven (6.9%) reported not performing GRT at any time. Of the 94 centres performing GRT, 52 (55.3%) sent blood samples to external laboratories. Notably, only 6/35 (17.1%) small centres had internal laboratories, compared to 14/35 (40.0%) medium centres and 22/24 (91.7%) large centres (P < 0.001). Most centres requested GRT for treatment-naïve individuals and all cases of virological failure. Only 24 (25.5%) requested GRT of HIVDNA before treatment changes. Regarding virological failure, most centres (38, 40.4%) requested GRT when HIV-RNA levels exceeded 200 copies/mL, while 26 (27.7%) requested it at levels exceeding 50 copies/mL. Additionally, 18 (19.1%) and 12 (12.8%) centres requested GRT at thresholds of 500 copies/mL and 1000 copies/mL, respectively. Regarding the specific GRT test used, 34 (36.2%) were unsure, while 16 (17.0%) reported using both next-generation sequencing and Sanger methods. Furthermore, 30 (31.9%) and 14 (14.9%) centres exclusively used next-generation sequencing and Sanger, respectively. Most centres reported receiving GRT results within 1 month (n = 72, 76.6%), while 22 (23.4%) centres obtained results within 2 weeks. However, 22 (23.4%) centres typically experienced more than 1-month delays. Finally, most participants (86, 91.5%) regarded GRT as a crucial routine test for the treatment of naïve people living with HIV. Conclusions: This study demonstrates that most Infectious Diseases Units in Italy continue to consider GRT an essential test for newly diagnosed people living with HIV in clinical practice. However, the utilization of GRT on HIV-DNA remains limited. Further efforts are required to decrease turnaround time in centres experiencing prolonged delays in obtaining results.